Analisis Pengelolaan Keuangan Desa Di Desa Tanjung Bunga Kecamatan Pangururan Kabupaten Samosir - Sitanggang, Tiur Yunita Sari; Hutapea, Herti Diana; Siboro, Danri Toni (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Village Financial Management is all activities which include planning, implementation, administration, reporting and accountability of village finances in order to achieve organization goals that have been set. This research aims to determine and analyze village financial management in Tanjung Bunga village Pangururan District Samosir Regency, whether it is in accordance with Permendagri no 20 of 2018. This research is qualitative research with comparative data analysis. Data collection methods include interviews with the 3village head, village secretary, head of finance,head of the government section, and the village consultative body (BPD) and documentation in the form of a realization report on the implementation of the village revenue and expenditure budget, a village owned wealth report, and a realization report on the Tanjung village government’s village budget fiscal year 2023. The result of the research show that village financial management in Tanjung Bunga village Pangururan district samosir regency in planning, administration, reporting and accountability is in accordance with Permendagri No 20 of 2018 , but the implementation of village financial management is not yet fully inaccordance with Permendagri No 20 Tahun 2018. Because the kaur dan kasi implementing budget activities submitted the draft list of budget implementation changes (DPPA) to the village head later than the provisions of Permendagri N0 20 of 2018. This is still within reasonable limits and can be used as evaluation material for the Tanjung Bunga to pay more attention to applicable regulation